Vasoactive intestinal peptide suppresses the NLRP3 inflammasome activation in lipopolysaccharide-induced acute lung injury mice and macrophages - Yong Zhou; Chen‐Yu Zhang; Jia‐Xi Duan; Qing Li; Hui‐Hui Yang; Chen‐Chen Sun; Jun Zhang; Xiaoqin Luo; Shaokun Liu (2019)
Vasoactive intestinal peptide (VIP) is a neuropeptide that exerts anti-inflammatory functions. We have reported that VIP mediated by lentivirus attenuates acute lung injury (ALI) in lipopolysaccharide (LPS)-induced murine model. However, the exact role of VIP in uncontrolled inflammation during ALI is largely unknown. Accumulating evidence indicates that the NLRP3 inflammasome has a critical role during ALI. In this study, we investigated the effects of VIP on the activation of NLRP3 inflammasome during the development of ALI in mice. Seven days after the intratracheal injection of VIP-lentivirus, a murine ALI model was induced by intratracheal injection of LPS. VIP-lentivirus significantly reduced the expression of NLRP3 inflammasome components in lung tissue, including NLRP3, pro-caspase-1, pro-IL-1β, and pro-IL-18. VIP-lentivirus also inhibited the formation of caspase-1 p10 and the maturation of IL-1β and IL-18. In vitro, exogenous VIP pre-treatment inhibited the priming of NLRP3 inflammasome in murine primary peritoneal macrophages, indicated by down-regulation of expression of NLRP3 inflammasome components. VIP pre-treatment effectively prevented the LPS-induced degradation of I-κB and the synthesis of the downstream of NF-κB, including TNF-α and IL-17A. Furthermore, VIP pre-treatment pronouncedly suppressed the autoproteolysis of caspase-1 and the secretion of IL-1β and IL-18 induced by LPS plus ATP in macrophages. In addition, VIP inhibited the generation of reactive oxygen species in macrophages by decreasing NOX1 and NOX2 expression. These findings illustrate one mechanism that VIP attenuates ALI induced by LPS through inhibiting the activation of the NLRP3 inflammasome and encourage further studies assessing the therapeutic potential of VIP to ALI.